The sweet far thing - Bray, Libba; OverDrive, Inc. (2007)
At Spence Academy, sixteen-year-old Gemma Doyle continues preparing for her London debut while struggling to determine how best to use magic to resolve a power struggle in the enchanted world of the realms, and to protect her own world and loved ones.
Title from eBook information screen.
640L
Decoding demand: 98 (very high) Semantic demand: 100 (very high) Syntactic demand: 87 (very high) Structure demand: 89 (very high)
Accelerated Reader AR
Electronic reproduction.
Keywords: Magic -- Fiction; Boarding schools -- Juvenile fiction; Schools -- Fiction; England -- Social life and customs -- 19th century -- Juvenile fiction; Electronic books; Paranormal fiction